ANALISIS DAN TANTANGAN HUKUM DI ERA DIGITAL DALAM TREND E-COMMERCE (STUDI KASUS PADA GEN Z) - Ayendri Serley Marcelia; Ali Maskur (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
This research aims to analyze legal challenges in the digital era, especially in the e-commerce trend. The case study in this research is Gen Z. The research method used is a qualitative method. Statistical data on electronic trading activities (e-commerce) shows an increase every year. This is in line with the development of information and communication technology and the improvement of communication infrastructure networks. An electronics-based economy has high potential for Indonesia, and is one of the backbones of the national economy. This research tries to analyze the problems of legal challenges in the e-commerce business and the role of the government in supporting the birth of new e-commerce business actors. This research uses a qualitative approach, descriptive analysis in the form of desk study research. The research results concluded that: first, legal challenges in developing e-commerce, namely: legal entity form, licensing; aspects of legality and legal protection of parties in the e-commerce community; and second, the government's role in developing e-commerce businesses is to improve the national legal system.